Melatonin intervention to prevent delirium in the intensive care units: a systematic review and meta-analysis of randomized controlled trials - Duan, Yushan; Yang, Yuan; Zhu, Weihua; Wan, Linjun; Wang, Gang; Yue, Jinxi; Bao, Qi; Shao, Jianlin; Wan, Xiaohong (Frontiers in Endocrinology, 2023)
Objective: To determine the preventive effect of melatonin on delirium in the intensive care.Methods: We conducted a systematic search of the PubMed, Cochrane Library, Science, Embase, and CNKI databases, with retrieval dates ranging from the databases' inception to September 2022. Controlled trials on melatonin and placebo for preventing delirium in the intensive care units were included. The meta-analysis was performed using Review Manager software (version 5.3) and Stata software (version 14.0).Results: Six studies involving 2374 patients were included in the meta-analysis. The results of the meta-analysis showed that melatonin did not reduce the incidence of delirium in ICU patients (odds ratio [OR]: 0.71; 95% confidence interval [CI]: 0.46 to 1.12; p = 0.14). There was a strong heterogeneity between the selected studies (I 2 =74%). Subgroup analysis results showed that melatonin reduced the incidence of delirium in cardiovascular care unit (CCU) patients (OR: 0.52; 95% CI: 0.37 to 0.73; p=0.0001), but did not in general intensive care unit (GICU) patients (OR: 1.14; 95% CI: 0.86 to 1.50; p=0.35). In terms of the secondary outcomes, there were no significant differences in all-cause mortality (OR: 0.85; 95% CI: 0.66 to 1.09; p=0.20), length of ICU stay (mean difference [MD]: 0.33; 95% CI: -0.53 to 1.18; p=0.45), or length of hospital stay (MD: 0.51; 95% CI: -1.17 to 2.19; p=0.55). Conclusion: Melatonin reduced the incidence of delirium in CCU patients, but did not significantly reduce the incidence of delirium in GICU patients.